2018
DOI: 10.1002/pbc.27419
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behavior impaired in children with low‐grade glioma

Abstract: At the group level, adaptive functioning of children with LGG is impaired compared with family controls. Regular structured monitoring of adaptive behavior is recommended to be able to define the needs for tailored rehabilitation in daily life at home as well as at school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous studies among PBTS with a comparable follow-up time (1–15 years) did report that recurrent neurosurgery, shunt revisions, and chemotherapy were associated with major disabilities and poorer motor skills. 3 , 15 , 28 We found these factors to be associated with fatigue in our cohort but not with participation or impairments in functioning. A potential explanation is the heterogeneity of our cohort with various types of brain tumors and/or overlap between treatment modalities, which challenges detecting relationships.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Previous studies among PBTS with a comparable follow-up time (1–15 years) did report that recurrent neurosurgery, shunt revisions, and chemotherapy were associated with major disabilities and poorer motor skills. 3 , 15 , 28 We found these factors to be associated with fatigue in our cohort but not with participation or impairments in functioning. A potential explanation is the heterogeneity of our cohort with various types of brain tumors and/or overlap between treatment modalities, which challenges detecting relationships.…”
Section: Discussionmentioning
confidence: 46%
“…We found that younger age at diagnosis (<6 years) was associated with more impairments in functioning, which is in accordance with previous studies in PBTS where younger age at treatment has been related to more disability. 3 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…There was a significant level of heterogen ity across the different studies (I 2 = 54%, p < 0.01) and no significant publication bias w identified t (15) = 0.36, p = 0.72, Figure S5a. 2021) [83] reported more than o independent cohort in their study [24,30,36,37,39,40,42,43,[45][46][47]49,[55][56][57][58]60,61,[63][64][65][66][70][71][72][73][74][75]77,83]. (a) Abso-lute risk-attention problems; (b) Absolute risk-emotional; (c) Absolute risk psychosocial problems…”
Section: Absolute Risk-attention Problemsmentioning
confidence: 98%
“…The publication bias was n significant, as revealed by Egger's test t (18) = 0.92, p = 0.369 (Figure S6a). 2021) [83] reported more than one independent cohort in their study [24,30,36,37,39,40,42,43,[45][46][47]49…”
Section: Standard Mean Difference-attention Problemsmentioning
confidence: 99%
See 1 more Smart Citation